Vegetation index and climate change: a multi-temporary evaluation of landsat images in the Paucarani lagoon in the period 1972 to 2018 - Mamani Vargas, Alejandro Jean Pier (2021)
The research evaluated the relationship between vegetation indexes and climate change by making a multitemporal evaluation of Landsat images for the period 1972 - 2018 in the Paucarani lagoon, Tacna. The information used corresponds to satellite images Landsat 5 and Landsat 8 level 1 T corrected in level of surface reflectance selected from the Google Earth Engine platform where the normalized difference vegetation index "NDVI" was generated for the years 1986, 1995, 2010 and 2018; and also the normalized difference water index “NDWI”. The results indicate that the highest mean NDVI values correspond to the months of December to May with values equal to or greater than 0.1, on the contrary, in the months of July and August the mean NDVI values decrease, presenting the year 1986 the value of 0.078 and the year 2018 the value of 0.065. From the precipitation values it was verified that these present a cyclical frequency with wet and dry years. With respect to the frequency of precipitation it was determined that the year 1986 presents frequency of precipitation from December to April compared to the year 2018 that presents frequency for the months of January and February. From the annual average minimum temperature values, it was verified that these present an increasing trend from 2012 with values lower than -6.50 ° C compared to values of up to -12.4 ° C present in previous years. It was concluded that the variable precipitation, minimum temperature and the values of the vegetation index "NDVI" present a relationship with a degree of significance <0.05 according to Pearson